2016
DOI: 10.3389/fpsyg.2016.00677
|View full text |Cite
|
Sign up to set email alerts
|

Affect and Subsequent Physical Activity: An Ambulatory Assessment Study Examining the Affect-Activity Association in a Real-Life Context

Abstract: Traditionally, cognitive, motivational, and volitional determinants have been used to explain and predict health behaviors such as physical activity. Recently, the role of affect in influencing and regulating health behaviors received more attention. Affects as internal cues may automatically activate unconscious processes of behavior regulation. The aim of our study was to examine the association between affect and physical activity in daily life. In addition, we studied the influence of the habit of being ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 47 publications
(85 reference statements)
5
54
1
Order By: Relevance
“…Recently, the role of affective and physical feeling states in influencing free-living physical activity has received increasing attention (Liao et al, 2015). A study in working adults found that greater positive affective states predicted more time spent in subsequent MVPA, while greater negative affective states predicted less time spent in subsequent MVPA (Niermann et al, 2016). Another study among college students revealed that increased positive affect and feeling energized were associated with a decrease in physical activity levels over the following 45 minutes (Kanning & Schoebi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of affective and physical feeling states in influencing free-living physical activity has received increasing attention (Liao et al, 2015). A study in working adults found that greater positive affective states predicted more time spent in subsequent MVPA, while greater negative affective states predicted less time spent in subsequent MVPA (Niermann et al, 2016). Another study among college students revealed that increased positive affect and feeling energized were associated with a decrease in physical activity levels over the following 45 minutes (Kanning & Schoebi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed earlier, we define self-control not only as the ability to inhibit attractive but undesired behaviors (e.g., unhealthy snacking), but also as the ability to initiate unattractive but desired behaviors (e.g., exercising). While positive emotions have been shown to benefit both initiatory and inhibitory self-control behaviors (Garg et al, 2007;Niermann et al, 2016), we are not aware of any research examining whether the effects of emotions on self-control are moderated by the type of self-control required. However, evidence suggests that inhibitory and initiatory self-control are related but yet distinct constructs (r = .68; de Ridder et al, 2011), which predict different outcomes .…”
Section: Emotions and Initiatory And Inhibitorymentioning
confidence: 97%
“…For example, Vinci et al (2017) found in an ecological momentary assessment study that smokers who experienced high levels of positive emotions were less likely to lapse, and Niermann, Herrmann, von Haaren, van Kann, and Woll (2016) found in an ambulatory assessment study that people who experienced high levels of positive emotions after work spent more time exercising that day, whereas the reverse was true for negative emotions. For example, Vinci et al (2017) found in an ecological momentary assessment study that smokers who experienced high levels of positive emotions were less likely to lapse, and Niermann, Herrmann, von Haaren, van Kann, and Woll (2016) found in an ambulatory assessment study that people who experienced high levels of positive emotions after work spent more time exercising that day, whereas the reverse was true for negative emotions.…”
Section: Can Emotions Facilitate Self-control?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies [21] also reported the opposite patterns. In terms of directionality of the effect, [22] and [23] showed that feeling more positive predicted more subsequent physical activity.…”
Section: Introductionmentioning
confidence: 99%